Program-targeted approach to managing financial risks of sustainable development based on corporate social responsibility in the decade of action - Liudmila I. Khoruzhy; Valery I. Khoruzhy; Bogdan S. Vasyakin; Wenhao Shen (Risks, 2022)
This paper aims to find the prospects of improving the practice of managing financial risks of sustainable development in the Decade of Action. We substantiate-based on economic and mathematical modeling based on a sample of 185 countries-that the existing (project-based) approach to managing financial risks of sustainable development, which was successfully implemented in the pre-crisis period (2015-2019), demonstrates reduced effectiveness at the beginning of the Decade of Action (2020-2021). This showed a marked increase in the overall level of financial risk, as well as an increase in the importance of private investment, in financing sustainable development in the first two years of the Decade of Action (220-2021) compared to 2018-2019. Additionally, the features of the continents are identified: Africa, America and the Caribbean, Asia, and Europe, and specific recommendations are proposed for them on the financial risk management of sustainable development in the Decade of Action. This paper's originality lies in the development of a new program-targeted approach to managing financial risks of sustainable development, which, due to its increased flexibility and the use of the market mechanism-is optimal for the conditions of the pandemic and will allow the ensuring of the full-scale (quantitative characteristics) financial provision of the SDGs in the Decade of Action using private investments. This paper's novelty is also due to the recommendation on the improvement of financial risk management based on corporate social responsibility (qualitative characteristics) to support the implementation of the SDGs in the Decade of Action.
Keywords: 330; corporate social responsibility; sustainable development; Decade of Action; management of financial risks; program-targeted approach